Participatory Research of Children as Participatory Process - Zwiernik, Jolanta (INSTED: Interdisciplinary Studies in Education & Society, 2018)
The problem discussed in this text is focused on participatory research carried out by children. They have been recently gaining popularity as another way of approaching childhood research, after researching children, conducting research on children and research with children. The article presents the genesis of participatory research practices, their characteristic features and describes the procedure of investigations conducted by children. Another discussed question concerns ethical and methodological dilemmas that accompany children?s participatory research. The final part of the considerations indicates advantages experienced by children carrying out the research which compose competencies that support civic participation of young researchers, now and in future.